2020
DOI: 10.1021/acs.jmedchem.0c00352
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases as New Targets in Alzheimer’s Disease: Opportunities and Challenges

Abstract: Although matrix metalloproteinases (MMPs) are implicated in the regulation of numerous physiological processes, evidences of their pathological roles have also been obtained in the last decades, making MMPs attractive therapeutic targets for several diseases. Recent discoveries of their involvement in central nervous system (CNS) disorders, and in particular in Alzheimer's disease (AD), have paved the way to consider MMP modulators as promising therapeutic strategies. Over the past few decades, diverse approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 222 publications
(471 reference statements)
1
38
0
Order By: Relevance
“…Our current data suggest that MT5-MMP can also control inflammation per se in a non-pathological state in a human setting, but it remains an open question whether basal downregulation of inflammatory markers predisposes astrocytes to decreased reactivity. In any case, our results reinforce the idea that MT5-MMP is not only an APP-cleaving enzyme but also that its scope of activity goes far beyond that [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our current data suggest that MT5-MMP can also control inflammation per se in a non-pathological state in a human setting, but it remains an open question whether basal downregulation of inflammatory markers predisposes astrocytes to decreased reactivity. In any case, our results reinforce the idea that MT5-MMP is not only an APP-cleaving enzyme but also that its scope of activity goes far beyond that [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 85%
“…Matrix metalloproteinases (MMPs), enzymes controlling intracellular and extracellular amyloidogenic protein turnover, are associated with neurodegenerative diseases [ 11 , 12 ]. Recently, we shed light on MT5-MMP as just such a novel therapeutic target [ 12 , 13 , 14 ]. In good health, MT5-MMP is a multifunctional MMP with N-cadherin substrate specificity that is mainly expressed in developmental stages and remains high in adulthood in the hippocampus and cerebellum [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activated MMPs remodel the pericellular environment by regulating the extracellular matrix (ECM) and the tight junction's breakdown. The MMPs also interact and alter the properties of growth factors, cell surface components, and signaling molecules, leading to neuroinflammation, cell death, and neurotoxicity [50]. In this context, separate studies conducted by Duits et al, 2015 [51] and Whelan et al, 2019 [52] showed a significant increase in MMP-10 in AD-dementia Aβ+ MCI patients as compared to cognitively normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, selectivity has become one of the principal aspects of MMP inhibitor design. In addition, various molecules acting against two or more MMPs have recently been investigated, suggesting that carefully selected multitarget approaches also represent a promising strategy for targeting MMPs [16].…”
Section: Introductionmentioning
confidence: 99%